2017
DOI: 10.1089/fpd.2016.2264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance, and Relatedness of Salmonella Isolated from Chickens and Pigs on Farms, Abattoirs, and Markets in Sichuan Province, China

Abstract: This study aims at investigating the distribution, antimicrobial resistance, and genetic relationship of Salmonella isolated from 18 farms, their downstream abattoirs, and markets of chickens and pigs in Sichuan province, China. A total of 193 Salmonella isolates were identified from 693 samples with an isolation rate of 26.27% (88/335) in chickens and 29.33% (105/358) in pigs. Salmonella was isolated more frequently in abattoirs and markets than from farms. Serotypes were determined according to the White-Kau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
9
32
1
1
Order By: Relevance
“…Among them, ST40 (38·27%), ST34 (18·41%) and ST469 (14·46%) were dominant. These results are consistent with some other studies showing that ST40 and ST34 are the most prevalent STs among pig isolates in China (Ma et al ). It is worth noting that ST469, which has been spreading in European countries, is becoming more prevalent in pork samples from its first detection in China (Ma et al ; Patchanee et al ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among them, ST40 (38·27%), ST34 (18·41%) and ST469 (14·46%) were dominant. These results are consistent with some other studies showing that ST40 and ST34 are the most prevalent STs among pig isolates in China (Ma et al ). It is worth noting that ST469, which has been spreading in European countries, is becoming more prevalent in pork samples from its first detection in China (Ma et al ; Patchanee et al ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with some other studies showing that ST40 and ST34 are the most prevalent STs among pig isolates in China (Ma et al ). It is worth noting that ST469, which has been spreading in European countries, is becoming more prevalent in pork samples from its first detection in China (Ma et al ; Patchanee et al ). Our results also revealed that the ST distributions were similar between strains from retail markets and wholesale markets, except that ST34 was more prevalent among wholesale market strains, indicating similar risk of Salmonella contamination between the two different markets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Few studies regarding the characterization of the Meleagridis serovar and a plausible explanation of why this serovar is so isolated in swine are found in the literature. Some studies (90)(91)(92)(93) have reported S. Meleagridis is one of the most prevalent in pork serovars, and its characterization by MLST indicates ST463 and ST64 with an MDR profile.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, many clinical epidemiologists are adopting the One Health concept in molecular surveillance studies due to the increasing realization that antibiotic resistance in the environment can be transferred to animals and humans or vice versa . In addition, there has been a debate on the possible impact of agricultural and veterinary use of antibiotics on human medicine; as well, the clinical importance of antimicrobial resistance genes found in the environment has been discussed …”
Section: Introductionmentioning
confidence: 99%